2004
DOI: 10.1042/bj20031043
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent protein kinase IIdelta associates with the ryanodine receptor complex and regulates channel function in rabbit heart

Abstract: Cardiac ryanodine receptors (RyR2s) play a critical role in excitation-contraction coupling by providing a pathway for the release of Ca(2+) from the sarcoplasmic reticulum into the cytosol. RyR2s exist as macromolecular complexes that are regulated via binding of Ca(2+) and protein phosphorylation/dephosphorylation. The present study examined the association of endogenous CaMKII (calcium/calmodulin-dependent protein kinase II) with the RyR2 complex and whether this enzyme could modulate RyR2 function in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 42 publications
7
91
0
3
Order By: Relevance
“…This leads to increased RyR channel opening in bilayers and to an increased Ca 2+ spark frequency in myocytes at a given SR Ca 2+ content [3,19,34,[48][49][50]. Controversy remains about which RyR amino acid is the critical CaMKII target (Ser2809 vs. Ser2815) [19,48,49].…”
Section: Ncx Mediated Ca 2+ Extrusion Counteracts Faster Sr Ca 2+ Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…This leads to increased RyR channel opening in bilayers and to an increased Ca 2+ spark frequency in myocytes at a given SR Ca 2+ content [3,19,34,[48][49][50]. Controversy remains about which RyR amino acid is the critical CaMKII target (Ser2809 vs. Ser2815) [19,48,49].…”
Section: Ncx Mediated Ca 2+ Extrusion Counteracts Faster Sr Ca 2+ Uptakementioning
confidence: 99%
“…CaMKII is known to associate with ryanodine receptors (RyRs) [3,4], L-type Ca 2+ channels [5][6][7] and possibly phospholamban (PLB) [8]. This basal localization near targets may be important for efficient and specific regulation of these CaMKII effector proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is known that CaMKII can be associated to RyRs (16,17), we tested whether CaMKII-dependent modulation of SAP97 trafficking was correlated to activation of RyRs by examining the distribution pattern of SAP97 in neurons exposed to caffeine (Fig. 4).…”
Section: Differential Distribution Of Maguk Family Members In Hip-mentioning
confidence: 99%
“…In this study, our findings revealed that there was a significant reduction of CaMKII levels in the acute phase of ischemia, which might decrease the activation of LTCC and RYR2 and intracellular Ca 2 + concentration. Phospho-CaMKII may promote activation of RYR2 of the SR, thereby increasing RyR2 Ca 2 + sensitivity and spontaneous release of Ca 2 + from internal storage (Currie et al, 2004). Further, phospho-CaMKII could cause increased PLB phosphorylation at T 17 , which might help preserve SR Ca 2 + , and disabled PLB's ability to inhibit SERCA2a, thereby increasing Ca 2 + reuptake into intracellular stores (Schwoerer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Ryanodine receptor 2 (RYR2) was a CaMKII-regulated protein that was involved in the regulation of the intranuclear Ca 2 + concentration. Currie et al (2004) have reported that CaMKII may promote activation of RYR2 of the sarcoplasmic reticulum (SR), thereby increasing RyR2 Ca 2 + sensitivity and spontaneous release of Ca 2 + from internal stores. The PLB was also defined as a CaMKII-regulated phosphoprotein (Sag et al, 2007).…”
Section: Discussionmentioning
confidence: 99%